1991
DOI: 10.1007/bf01418882
|View full text |Cite
|
Sign up to set email alerts
|

A generalisation of the theory of geometrical shock dynamics

Abstract: Abstract. The study of the propagation of a shock down a tube of slowly varying cross sectional area has proved to be most valuable in understanding the dynamics of shocks. A particular culmination of this work has been the theory of geometrical shock dynamics due to Whitham (1957Whitham ( , 1959. In this theory the motion of a shock may be approximately computed independently of a determination of the flow field behind the shock. In this paper the propagation of a shock down such a tube is reconsidered. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 15 publications
0
42
0
Order By: Relevance
“…The shock adjusts itself to changes in the geometry only [29]. As explained by Best [8], Whitham considered the motion of a shock into a uniform gas at rest, down a tube of slowly varying cross sectional area, A, and under some physically grounded hypothesis, he obtained an expression relating the local shock Mach number, M, to A, now known as the A-M relation [31] (see also (9) and (4)). The GSD model reads…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shock adjusts itself to changes in the geometry only [29]. As explained by Best [8], Whitham considered the motion of a shock into a uniform gas at rest, down a tube of slowly varying cross sectional area, A, and under some physically grounded hypothesis, he obtained an expression relating the local shock Mach number, M, to A, now known as the A-M relation [31] (see also (9) and (4)). The GSD model reads…”
Section: Introductionmentioning
confidence: 99%
“…In practice, GSD has proven to be fairly accurate for diffraction around a corner, non-regular Mach reflection [29], or accelerating shocks and shown only little deviation for expanding decelerating flows [5]. Whitham's model has been extended to take into account unsteady flow behind the shock [8,9,10], non-uniform gases properties [20], and has been applied, among others, to imploding shock waves [11,1], atmospheric propagation [7], detonation in explosives [2,3,6], supersonic engine unstart [27] and astrophysics [14].…”
Section: Introductionmentioning
confidence: 99%
“…͑2.5͒ was assumed to be independent of entropy. On the other hand, Holl 3 and Best 20 use the Rankine Hugoniot relation for the conservation of energy to write an over-determined system which they use to derive A(M ) for water. Cates 18 has shown that this approach can lead to unnecessary error when calculating the Mach number from pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The truncated system, which is closed, can be regarded as a good approximation of the infinite hierarchy of the system governing shock propagation [22]. It is worth mentioning that an infinite sequence of ordinary differential equations, which hold on the shock front, was also derived by Best [31] in an attempt to describe shock motion in one dimension. However, his approach, unlike the one presented here, is based on CCW approximation and admits the fact that the application of a C + characteristic equation at the shock is somewhat ad-hoc.…”
Section: Since the Coupling Term (N · ∇P)mentioning
confidence: 99%